HUBUNGANÂ ANTARA STATUS GIZI DENGAN USIA MENARCHE DI SDN CANGGU II MOJOKERTO - Wahyuningrum, Tria (JURNAL KEPERAWATAN BINA SEHAT, 2009)
Downhill age menarche at this century half. As for factors influencing age menarche is clan, circumstance gizi, public health, environmental factor, climate and nation. factor of Circumstance gizi can influence the age menarche. In last a decay this is age menarche have shifted to more young age, from 17 year become 12 year. That matter because of status gizi.This Research target is to know the relation of between status gizi with the age menarche in SDN Canggu II Mojokerto.This desain research is analytic with the study of cross sectional. Its population is all schoolgirl of class of V and VI experience of the menarche. Sampelnya is some of schoolgirl of class of V and VI experience of the menarche that is as much 27 one who is taken with the technique of Simple Random Sampling. Data collecting of through test of correlation of Rank Spearman with the meaning storey level 0,05.From research result got by that responder which have status to good gizi that is as much 22 people ( 81,48 %) and almost all from responder experience of the normal menarche that is as much 21 people ( 77,7 %). From result test the correlation of Rank Spearman got by result that P ( 0,028) < a ( 0,05), hence H1accepted by a becoming there is relation of between status gizi with the age menarche. From the research result is hence expected at health worker require to socialize the public guidance of well-balanced gizi and also sanitary knowledge require to be given early possible.Keyword : status gizi, age menarche